Hesitancy for Adult Vaccines Among Healthcare Providers and their Family Members in Delhi, India: A Cross-Sectional Study - Nikhita Kalra; Tanisha Kalra; Suruchi Mishra; Saurav Basu; Nidhi Bhatnagar (Elsevier, 2022)
Objectives: Adult immunisation has recently emerged as an area of emphasis in research and policy. Increasing life expectancy, outbreaks like COVID-19, and the endemic nature of diseases like dengue, malaria have underscored its importance. Therefore, this study was carried out to assess hesitancy and the factors influencing the uptake of vaccines in adults. Methods: A descriptive cross-sectional study was conducted among the medical students and doctors affiliated to a medical college and tertiary care hospital in Delhi, India and their immediate family members in January 2021. Online data collection was done using the Google Form platforms. Data on awareness and perceptions regarding adult vaccination and immunisation status of participants was collected. The dataset was exported in the Microsoft Excel format and analysed with IBM SPSS Version 25 (Armonk, NY: IBM Corp). Results: A total of 461 adults responded to the survey. The most common reasons for vaccine hesitancy were fear of side effects (51.41%), lack of awareness of vaccines (49.46%), and the lack of national guidelines on adult vaccination (32.97%). Hesitancy for vaccines among those who were informed by healthcare workers of vaccine availability was highest for zoster vaccine (97.80%) and least for tetanus toxoid (57.62%). Significant hesitancy was also observed for pneumococcal, human papillomavirus, influenza and varicella vaccines. Conclusions: Reduced vaccine uptake due to vaccine hesitancy in adulthood is a major health concern. Framing national guidelines for adult vaccination in India and awareness generation to create a public demand for adult vaccination warrants prioritization.